Kinetics and Mechanism of Oxidation of para-Substituted Benzaldehydes by Quinolinium Bromochromate in Aquo-acetic Acid Medium - Hiran, B.L.; Malkani, R.K.; Chaudhary, Pakaram; Verma, Palak; Shorger, Neetu (Asian Journal of Chemistry, 2010)
Oxidation of para substituted benzaldehydes by quinolinium bromochromate (QBC) leading to corresponding benzoic acids is first order with respect to QBC and the benzaldehydes while second order with respect to [H+]. The oxidation of deuterated benzaldehyde exhibits a substantial primary kinetic isotope effect. The decreasing order of reactivity in low acidic solution for the benzaldehydes is p-NO2 > p-Cl > H > p-OH > p-OCH3. The results of correlation analyses point to an electron deficient reaction centre in the transition state. Formation of chromic-ester between hydrated benzaldehydes and protonated quinolinium bromochromate, followed by C––H bond fission in rate determining step, has been suggested. Activation parameters have also been evaluated.